Simplified approach for determination of parameters for Kostiakov's infiltration equation - Mekonen Ayana Gebul (Water Practice and Technology, 2022)
Knowledge of soil infiltration characteristics is required increasingly for the proper design and efficient management of irrigation. Various empirical and physically based infiltration models have been used for several years, but the practical use of many is limited by parameter determination problems, which, in turn, are influenced by factors acting at the surface and within the soil, initial and boundary conditions, etc. In this study, a simplified approach for determining parameters for the Kostiakov equation was tested and validated. The equation's linearized form, using logarithmic transformation and field data collected from five sites, was employed. The results show that cumulative infiltration can be described well using the approach. Its quality is also confirmed by performance indices like R2 and standard error, whose values ranged from 0.985 to 0.999 and 0.020 to 0.005, respectively, suggesting that the simplified approach described is sufficient for practical purposes, when data are too scarce to apply other, complex methods to predict cumulative infiltration. HIGHLIGHTS Knowledge of soil infiltration is needed for practical applications.; Infiltration models involve complex processes of parameter determination.; The modified Kostiakov equation (MKE) is widely used in irrigation.; Other empirical approaches fail to describe infiltration over long periods.; The simple approach explained here can accurately determine parameters of simplified MKE.;